Implementation of the Argentine Education Law Act 26206: Reasons that prompted its approval - Jofré, Andrea Romina (Universidad Nacional del Litoral, 2021)
This article addresses the most relevant aspects and circumstances that promoted the implementation of Law Act No. 26.206, weighing up the general context in Argentina towards 2006 and, in particular, the education scenario of the time. Thus a brief historical review of the evolution of education regulations is outlined to trace all rights granted from the sanction of Law Act No. 1.420, through the approval of Argentine Federal Law of Education, until reaching the current law in force, namely National Education Law. By means of the documentary research method and the assessment of theoretical sources, we provide a characterization of the Argentine education system after the implementation of each legal framework and the subsequent introduction of all implied changes. An analysis of the education policies implemented at certain time periods is also included with the aim of contributing to a higher educational quality. This document is intended to shed light on the decline of the previous Education Law Act No. 24195 in the face of social and political demands as one of the main foundations for the implementation of the current regulatory framework